Evaluation Of A 10-Week Nutrition Education Intervention In University Students: Outcomes On Nutrition-Related Quality Of Life - Pei Lin, Lua; Mohd Razif, Shahril; Wan Putri Elena, Wan Dali (2014)
Objective: The purpose of this study was to evaluate the effectiveness of nutrition education intervention among university students in terms of social, psychological factors and nutrition-related Quality of Life (NQoL) outcomes after receiving a 10-week nutrition education. Longitudinal and randomised study design was adopted for the study. Methods: A total of 417 respondents from four public universities in Terengganu were randomly assigned to either intervention group (IG = 205) or control group (CG = 212). The IG received nutrition education through three tools; 1) conventional lecture, 2) brochures and 3) text messages via short messaging system (SMS) while the CG not received any intervention. Students completed the Malay version of NQoL (6 domains; 49 items; Likert-type responses=1-5) and SF-36 (8 domains; 36 items) at pre-intervention and post-intervention. Data analysis was carried out by using SPSS 16.0 utilising descriptive and parametric statistics. Results: Ninety-one percent of participants (IG = 178; CG = 202) completed the study (age = 19.1±1.1 years; female = 87.6%; Malay = 98.2%). After controlling for possible confounders (eg. weight, waist, hip circumferences and pre-intervention scores for each domain), IG possessed relatively higher NQoL score in Food Impact (p = 0.001), Social / Interpersonal (p = 0.008), Physical Functioning (p = 0.011) and Overall NQoL (p = 0.001). However, Psychological Factors did not show any significant difference for both groups. Conclusion: Although the intervention did not generate significant impact in the psychological component over a period of 10 weeks, significant positive impacts in Social/Interpersonal aspects and NQoL were clearly shown. ASEAN Journal of Psychiatry, Vol. 15 (1): January – June 2014: 39-53.